2020
DOI: 10.3389/fneur.2020.00468
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Stroke Care in the Era of COVID-19

Abstract: The current coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has led to immense strain on healthcare systems and workers. Patients with severe symptoms of COVID-19 may also present with acute neurological emergencies such as ischemic stroke. Ischemic stroke in these patients may result from COVID-19 related complications or decompensation of previously asymptomatic cerebrovascular disorders, or concurrent ischemic stroke from common stroke risk factors in a pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
0
14
0
4
Order By: Relevance
“…The increased risk of hypercoagulable states has resulted in the suggested addendums for COVID-19 patients at risk of cerebral vascular incidents. [ 107 , 108 , 109 , 110 ]. The documented endothelial injury, changes in circulating prothrombotic factors, and increased stasis resulting from immobilization due to COVID-19 infection have warranted hypervigilance in the monitoring and prophylactic treatment of these patients.…”
Section: Neurological Disorders and Their Management In Covid-19 Patientsmentioning
confidence: 99%
“…The increased risk of hypercoagulable states has resulted in the suggested addendums for COVID-19 patients at risk of cerebral vascular incidents. [ 107 , 108 , 109 , 110 ]. The documented endothelial injury, changes in circulating prothrombotic factors, and increased stasis resulting from immobilization due to COVID-19 infection have warranted hypervigilance in the monitoring and prophylactic treatment of these patients.…”
Section: Neurological Disorders and Their Management In Covid-19 Patientsmentioning
confidence: 99%
“…Our systematic review revealed a total of 45 studies reporting imaging features of a total of 483 COVID‐19 patients suffering from acute ischemic stroke (AIS) 12,18,21–24,30–67 . A total of 26 studies were presented as single case reports or as case series 30–55 . The remaining 19 studies were conducted as retrospective studies reporting on neuroimaging findings of AIS patients 12,18,21–24,56–66 .…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%
“…Estão descritos casos de doentes assintomáticos, e casos de doentes que apresentam quadros sintomatológicos que podem agregar: febre, tosse, anosmia, dispneia, pneumonia com envolvimento bilateral, insuficiência respiratória, lesões cardíacas, insuficiência renal ou encefalite. Mas, também já foram descritos casos de doentes cuja apresentação inicial foi um Acidente Isquémico Transitório (AIT) ou um Acidente Vascular Cerebral (AVC) (2,3) .…”
unclassified
“…Atendendo ao facto das patologias cardiovasculares constituírem uma das principais causas de morte e incapacidade em todo o mundo (10)(11)(12) , as quais requerem cuidados prioritários e triagem emergente (3,13) , que são determinantes para a realização de eventuais procedimentos invasivos (14) , urge perceber qual foi o impacto que a pandemia por COVID-19 teve no doente acometido por AVC.…”
unclassified
See 1 more Smart Citation